Endurance Trained Athletes Do Not per se Have Higher Hoffmann Reflexes Than Recreationally Active Controls - Bertschinger, Raphael; Giboin, Louis-Solal; Gruber, Markus (Frontiers in Physiology, 2021)
The impact of endurance training on spinal neural circuitries remains largely unknown. Some studies have reported higher H-reflexes in endurance trained athletes and therefore, adaptations within the Ia afferent pathways after long term endurance training have been suggested. In the present study we tested the hypothesis that cyclists (n = 12) demonstrate higher Hoffmann reflexes (H-reflexes) compared to recreationally active controls (n = 10). Notwithstanding, highly significant differences in endurance performance (VO2peak: 60.6 for cyclists vs. 46.3 ml/min/kg for controls (p<0.001) there was no difference in the size of the SOL H-reflex between cyclists and controls (Hmax/Mmax ratio 61.3 vs 60.0% respectively (p = 0.840). Further analyses of the H and M recruitment curves for SOL revealed a significant steeper slope of the M recruitment curve in the group of cyclists (76.2 ± 3.8° vs. 72.0 ± 4.4°, p = 0.046) without a difference in the H-recruitment curve (84.6 ± 3.0° vs 85.0 ± 2.8°, p = 0.784) compared to the control group. Cycling is classified as an endurance sport and thus the findings of the present study do not further support the assumption that long-term aerobic training leads to a general increase of the H-reflex. Amongst methodological differences in assessing the H-reflex, the training-specific sensorimotor control of the endurance sport itself might differently affect the responsiveness of spinal motoneurons on Ia-afferent inputs.